2014
DOI: 10.1002/mop.28185
|View full text |Cite
|
Sign up to set email alerts
|

Very low profile ultrawideband microstrip band‐stop filter

Abstract: In this article, a compact microstrip band‐stop filter with 3–11.2‐GHz bandwidth for ultrawideband applications is proposed. The microstrip filter configuration consists of a transmission line with a pair of C‐shaped strips as a stub, four arc‐shaped slots embedded inside them, and a ground plane. An excellent agreement between measured and simulated results was obtained. The proposed microstrip filter fabricated on a Rogers RT/Duroid 5880 substrate with a relative dielectric constant of 2.2 and has a very sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The upper frequency bandwidth is significantly affected using them. It is observed that using these modified elements including L‐shaped slits and parasitic structures, additional third (9.5 GHz), and fourth (13.7 GHz) resonances are excited and hence the bandwidth is increased .…”
Section: Resultsmentioning
confidence: 99%
“…The upper frequency bandwidth is significantly affected using them. It is observed that using these modified elements including L‐shaped slits and parasitic structures, additional third (9.5 GHz), and fourth (13.7 GHz) resonances are excited and hence the bandwidth is increased .…”
Section: Resultsmentioning
confidence: 99%
“…4. It is evident that the employed EBG is highly active in generating notches [29][30][31][32][33][34]. According to the current distribution at 5 and 8 GHz, it can be found that at the first notch, the currents are extremly active inside the EBG and at 8 GHz, the outer width of the EBG is surrounded by the surface current.…”
Section: Schematic Of the Proposed Bpf Designmentioning
confidence: 99%
“…Recently, DGS resonator improvement such as asymmetric structure has attracted a lot of attentions in filter designing to achieve better performances [14], [22]. Moreover, the microstrip filters with several periodic units of photonic-band-gap (PBG) structure are proposed in [23]- [26]. Stated thus, periodic DGS resonators can be used in flexible microstrip filter design to achieve better performances, e.g., reducing size, sharping TB, widening SB.…”
Section: Introductionmentioning
confidence: 99%